Google Site as a Tool for Teaching Undergraduate Students in Forensic Medicine - Pragnesh Parmar1 , Swapnil Patond2 , Gunvanti Rathod3 , Sudhir Ninave4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Today, students are well versed with use of internet and web based teaching can becomeimportant source to supplement traditional teaching. Web based teaching via google site can touch deeperaspect of learning by serving as good tool for revision.Objectives: To develop web based teaching module via google site and evaluate students’ performancebefore and after exposure to web based teaching module along with perceptions of students and facultieson it.Methods: Web based teaching module in Forensic Medicine on one topic of core competency (Mechanicalinjury) was developed and validated. Module contained lecture notes, photographs, etc. on google sites.Consent form, feedback form and pre-test and post-test Questionnaire (Total 10 multiple choice questions)were formed and validated. All the medical undergraduate students (5th semester) were subjected to pre-testquestionnaire, web based teaching module, post-test questionnaire followed by feedback after obtainingtheir informed written consent via google site. Feedback of faculties were also obtained and analysed.Results: Out of 138 participants, 84 were male and 54 were female. There was no statistically significantdifference between perceptions of male and female participants. Comparison of pre and post test scores ofstudents was done using Wilcoxon’s sign rank test. Students scored significantly more in post-test. Bothstudents and faculties gave positive feedback for web based teaching module.Discussion: Classroom traditional teaching is always limited to time, place, person and mood of studentswhile web based teaching via google site can be accessed by students on their own time, ease and pacewithout any limitation. Higher domain can be explored and in depth teaching is possible via web basedteaching.Conclusion: Web based teaching module via google site was found to be very useful to enhance teachingexperience of undergraduate students as good tool of revision.